1990
DOI: 10.1523/jneurosci.10-11-03743.1990
|View full text |Cite
|
Sign up to set email alerts
|

Multiple signal transduction mechanisms leading to the secretion of 5- hydroxytryptamine by MTC cells, a neurectodermally derived cell line

Abstract: Parafollicular (PF) cells of the thyroid gland are neural crest derivatives. These cells remain plastic even in adult animals and can be induced to exhibit neural properties when exposed to NGF in vitro. A human cell line derived from PF cells, medullary thyroid carcinoma (MTC), has previously been shown to synthesize and store 5-HT, a serotonin-binding protein (SBP), and several neuropeptides; moreover, when grown in impoverished media, MTC cells display neural properties. The purpose of the current study was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
29
0

Year Published

1992
1992
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 27 publications
1
29
0
Order By: Relevance
“…The pellet was solubilized in the above buffer containing Triton X-100 (1.0%). Proteins (100 g) were separated by 8.5% SDS-PAGE (Tamir et al, 1990). After separation, the proteins were electroblotted onto nitrocellulose membranes, and protein bands were visualized by staining the blots for 2 min in Ponceau solution (0.02% in 0.3% trichloroacetic acid).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The pellet was solubilized in the above buffer containing Triton X-100 (1.0%). Proteins (100 g) were separated by 8.5% SDS-PAGE (Tamir et al, 1990). After separation, the proteins were electroblotted onto nitrocellulose membranes, and protein bands were visualized by staining the blots for 2 min in Ponceau solution (0.02% in 0.3% trichloroacetic acid).…”
Section: Methodsmentioning
confidence: 99%
“…The CaR is G-protein-coupled (Herbert and Brown, 1995;Ruat et al, 1996) and has been demonstrated to be linked to Gi and Gq (Tamir et al, 1996). After the activation of the CaR by 1[Ca 2ϩ ] e , PF cells depolarize (as a result of an increase in a nonselective plasma membrane cation conductance) (McGehee et al, 1997), secretory vesicles acidify (Tamir et al, 1994b), and 5-HT is secreted (Tamir et al, 1990(Tamir et al, , 1994bMcGehee et al, 1997).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Mice and rats belong to these many species in which endogenous 5-HT has not yet been found in adult C cells, unless the thyroid gland is pretreated with 5-HTP. C cells store serotonin in the same secretory granules as calcitonin [41,176], where 5-HT is linked to a specific protein called serotoninbinding-protein (SBP) [41,[177][178][179]. Furthermore, C cells have been proposed as a serotonergic neuron study model since they exhibit some properties of serotonergic neurons, including biosynthesis and storing of serotonin and regulated release and expression of both the 5-HT autoreceptor and the 5-HT transporter [180].…”
Section: Serotoninmentioning
confidence: 99%
“…Another group showed that increased levels of TRH release calcitonin in normal PF cells as well as in MTC, similar to the effect of pentagastrin (12). Further, TSH leads to a discharge of serotonin in PF cells and MTC (4,6,13,14). On the other hand, serotonin receptors have been detected on the FRTL-5 follicular cell line.…”
Section: Introductionmentioning
confidence: 86%